Rapid and Scalable Lubrication Coating for Industrial and Medical Applications via Sequential Dip‐Coating - Yeontaek Lee; Kayoung Son; Yejin Jo; Seung Hyun Lee; Jeuhee Lee; Tae Young Kim; Seonghyeon Eom; Youn‐Hoo Hwang; Dae‐Eun Kim; Inhee Choi; Jung Seung Lee; Jungmok Seo (Advanced Materials Interfaces)
Abstract Surface coatings have been widely studied and applied in industrial and biomedical fields to give functionalities such as friction reduction, anti‐fouling, and enhanced biocompatibility. However, conventional coating techniques often suffer from limited material compatibility, non‐uniform coverage on complex geometries, labor‐intensive fabrication, and dependence on specialized equipment. In this study, Swift Lubrication is introduced for Industrial and Medical Equipment (SLIME), a rapid (≈10 s) two‐step dip‐coating method that employs an UV perfluoropolyether base coat followed by a slippery activation layer. SLIME enables the formation of ultra‐low friction surfaces, robust anti‐fouling properties, and effective diffusion barrier functionality without requiring intricate fabrication processes or specialized equipment. The versatility of SLIME coatings is demonstrated through their application on 3D‐printed molds, high‐viscosity storage containers, and various biomedical devices, highlighting their material‐independent applicability, excellent biocompatibility, and superior anti‐adhesion performance. This is envision that SLIME coatings will serve as a practical and scalable solution for an advanced surface lubrication method, significantly enhancing device durability, operational efficiency, and performance across industrial and biomedical applications.